Adherence to Clinical Practice Guidelines for the Treatment of Candidemia at a Veterans Affairs Medical Center - Ashong, Chester N.; Hunter, Andrew S.; Mansouri, M. David; Cadle, Richard M.; Hamill, Richard J.; Musher, Daniel M. (International Journal of Health Sciences, 2017)
Objectives: The primary objective of this study was to examine the appropriateness of candidemia management at a Veterans Affairs Medical Center as recommended by the 2009 Infectious Diseases Society of America (IDSA) guidelines for treatment of Candida infections. Methods: A retrospective analysis of 94 adult patients with blood cultures positive for Candida spp. was performed. Patients were stratified by severity of disease into two groups: non-neutropenic, mild-moderate disease (Group 1, n = 54, 56%) and non-neutropenic, moderate-severe disease (Group 2, n = 40, 42%). Results: Adherence to the IDSA recommendations for recommended antifungal drug, dose, and duration of therapy was low in both groups (16.7% in Group 1 and 17.5% in Group 2). Although adherence was not associated with higher clinical resolution of infection (P = 0.111), it was associated with a significantly lower mortality rate (P = 0.001) when compared to variance from the guidelines at 6 weeks. Conclusion: Although adherence to published guidelines for treating patients with candidemia was suboptimal at our institution, patients that were managed based on the guidelines had a statistically lower mortality rate.